Indonesian Marine Resources Law Perspective of Marine Tourism Development - I Dewa Gede Atmadja (Warmadewa Press, 2022)
Indonesia as an archipelagic country with an archipelago perspective has the second widest beach in the world, as well as a territorial sea area (archipelago waters) including the Exclusive Economic Zone (EEZ) and the Continental Shelf with rich and potential marine resources. in fulfilling the mandate of the Constitution to realize social justice for all Indonesian people (social justice principle). After the Covid outbreak subsided, tourism activities began to increase, providing a positive impact on the national and regional economy, including in the field of marine tourism (maritime tourism), including tourism activities on the waters that take advantage of high waves, namely for surfers (surfing), underwater activities for Diving tourists to enjoy the beauty of coral reefs and ornamental fish (diving to enjoy the coral reef and the ornamental fishing), this marine tourism destination is quite a lot provided by Indonesian nature, including on the island of Bali.